Toll-Like Receptors Gene Polymorphisms in Autoimmune Disease - Zhang, Yingchi; Liu, Jia; Wang, Changlun; Liu, Junxian; Lu, Wei (Frontiers in Immunology, 2021)
Toll-like receptors (TLRs) are important initiators of the immune response, both innate and acquired. Evidence suggests that gene polymorphisms within TLRs cause malfunctions of certain key TLR-related signaling pathways, which subsequently increases the risk of autoimmune diseases. We illustrate and discuss the current findings on the role of Toll-like receptor gene polymorphisms in numerous autoimmune diseases in this review, such as type 1 diabetes mellitus, Graves’ disease, rheumatoid arthritis, systemic lupus erythematosus and multiple sclerosis. The study of genetic variation in TLRs in different populations has shown a complex interaction between immunity and environmental factors. This interaction suggests that TLR polymorphisms affect the susceptibility to autoimmune diseases differently in various populations. The identification of Toll-like receptor gene polymorphisms can expand our understanding of the pathogenesis of autoimmune diseases, which will subsequently guide effective medical management and provide insight into prognosis and advanced treatments.